Cutting the Credit Line: Evidence from Germany - Volker Nitsch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The massive decline in international trade in 2008/09 is often attributed to the global deterioration in financial conditions after the bankruptcy of a US investment bank, Lehman Brothers. This paper examines the association between external finance and firm activity in Germany in more detail. In particular, we explore a novel data set that matches a full sample of quarterly bank-firm lending data with detailed information on borrowers and lenders. Our results indicate that foreign sales of German non-financial corporations are insensitive to variations in external finance. While German banks affected by the crisis have significantly reduced their credit supply, we only observe a causal (negative) effect on their clients' domestic sales. Exporting firms, in contrast, seem to be particularly good borrowers.
Keywords: F40; G21; E44; 330